Duty Drawbacks, Competitiveness and Growth : Are Duty Drawbacks Worth the Hassle? - Ianchovichina, Elena (World Bank, Washington, DC, 2012)
Many countries use duty drawbacks on exports, yet they have been given little attention in the literature and there is no consensus whether countries should embrace or abandon them. The author asserts that the answer depends on a country s development priorities and economic conditions. An increase in the drawback has a positive impact on export competitiveness and employment, but could lead to exports with low domestic value added. The welfare effects of duty drawback reform are ambiguous. An increase in the drawback is more likely to be welfare improving if the economy is small with high input tariffs, low initial drawback, low administrative costs, and leakages in the tariff collection system. In China duty drawback removal after meeting WTO commitments will deepen domestic supply chains and improve welfare, but will hurt China s economic efficiency, export competitiveness, and real factor incomes. Further liberalization could mitigate these negative effects.